Direct observation of t 2g orbital ordering in magnetite - Schlappa, Justina; Haverkort, Maurits W. (Physical review letters, 2008)
Using soft-x-ray diffraction at the site-specific resonances in the Fe L2,3 edge, we find clear evidence for orbital and charge ordering in magnetite below the Verwey transition. The spectra show directly that the (0012) diffraction peak (in cubic notation) is caused by t2g orbital ordering at octahedral Fe2+ sites and the (001) by a spatial modulation of the t2g occupation.